Analisis Resiko Pembiayaan dan Resolusi Syariah pada Peer-To-Peer Financing - Muhammad, Rifqi; Nissa, Izzun Khoirun (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This paper aims to discuss the implementation of Islamic fintech financing and the risks that potentially occur in Indonesia. Islamic fintech operational activities with a peer-to-peer (P2P) financing model and risk mitigation that can be done to minimize risk in Indonesia which makes MSME the main market segment. Furthermore, this study will discuss the development of Islamic fintech in Indonesia and more specifically its contribution nationally. This research will use a case study of one of the P2P platforms that was once awarded as the best Sharia fintech in providing services to MSMEs in Indonesia. Finally, it will be closed with sharia resolution in solving problem financing. This paper contributes to the development of sharia fintech because it provides an overview of the differences between sharia fintech risks and other sharia financial institutions because sharia fintech places more emphasis on risk sharing and does not make financial intermediation institutions as the single largest insurer of liquidity risk.